Gastrointestinal disorders in COVID-19 patients: a great imitator (Faculty of Medicine Universitas Indonesia, 2021)
Up to this point, the coronavirus disease 2019 (COVID-19) pandemic is still ongoing. Some studies with a large number of cases have reported its clinical manifestations, concluding that the disease is a great imitator. Patients may present with symptoms other than the main symptoms of respiratory tract infections, such as diarrhea, abdominal pain, nausea, or vomiting, which may sometimes cause a delayed treatment in managing COVID-19 patients. Reports of various hospitals have also demonstrated gastrointestinal complaints as a clinical manifestation in those patients. The patients may come with gastrointestinal symptoms as their early clinical manifestation, or the gastrointestinal symptoms may be found in hospitalized COVID-19 patients, which indeed can be explained since the SARS-CoV-2, an etiologic agent of COVID-19 infection, can obviously be found along the gastrointestinal tract. Hence, the virus can be found in fecal and anal, and therefore, rectal swabs can be used as a diagnostic tool for COVID-19 infection.